Efficacy and safety of various drug combinations in treating plaque Psoriasis: A meta-analysis [version 2; peer review: 2 approved] - Nayak Snehasis; Karshe Haji Ali; Pendyala Siri; Ngabo Herve; Sayed Zafar (F1000Research)
Background Psoriasis, a chronic inflammatory disease affecting the skin, joints, and nails (2-3% worldwide), significantly affects quality of life. Genetic and environmental factors also play key roles. Topical corticosteroids, calcineurin inhibitors, and oral corticosteroids help to manage plaque psoriasis symptoms, but combination therapies might offer greater effectiveness and improved safety profiles. These combinations could potentially reduce medication dosages and side effects in patients. Objective To assess the efficacy and safety of various drug combinations over conventional monotherapies in the treatment of moderate to severe plaque psoriasis, which incorporates palmoplantar psoriasis and psoriasis vulgaris, by discovering and utilizing research articles comprising the same or similar variables as PASI 75 and evaluating the information using RevMan v5.4.1. Method We reviewed the efficacy and safety of combination therapy vs. monotherapy/placebo for moderate-to-severe plaque psoriasis (palmoplantar and vulgaris) using PASI 75 via RevMan v5.4.1. Risk of bias assessment and funnel plots were employed to assess the heterogeneity of each paper. Inclusion criteria – Publications < 20yrs, RCTs, plaque/palmoplantar/psoriasis vulgaris; exclusion criteria – Guttate/arthritic psoriasis, pediatric and pregnant individuals, publications > 20 yrs. Results Seventeen studies were analyzed, comprising a total of 2291 patients (n=1147 with combination regimens and n=1144 with control regimen in the analysis). A significant PASI 75- response was observed in the pioglitazone combination subgroup as compared to placebo (OR=4.92,95% CI 2.19-11.05, P = 0.0001); methotrexate combination subgroup as compared to placebo (OR=2.56, 95% CI 1.67-3.94, P< 0.0001) test of subgroup differences showed P= 0.14, I2= 34%. Incidence rate of abnormality in levels of liver enzymes (OR=1.89,9.5% CI 6.69-5.22, P=0.22), nausea (OR=1.28,95% CI 0.77-2.14, P=0.34), headache (OR=1.28,95% CI 0.77-2.14, P=0.58), fatigue (OR=0.89, 95% CI 0.41-1.90, P=0.45).] Conclusion This study showed that combination therapy is very effective for plaque psoriasis, with promising combinations of pioglitazone. While safety seems similar between the groups, larger studies are needed to determine the long-term effects. These findings suggest that personalized treatment plans could improve outcomes; however, confirmation through larger trials is crucial before wider use. This opens doors to research on optimal combinations for individual patients.